2015
DOI: 10.1007/s11738-015-1957-x
|View full text |Cite
|
Sign up to set email alerts
|

Salt priming improved salt tolerance in sweet sorghum by enhancing osmotic resistance and reducing root Na+ uptake

Abstract: This study attempted to explore how salt priming affected salt tolerance in sweet sorghum with emphasis on root Na ? uptake. After 10 days of pretreatment with 150 mM NaCl, plants were stressed with 300 mM NaCl. After salt stress for 7 days, dry matter of root and shoot decreased by 58.7 and 69.7 % in non-pretreated plants and by 37.9 and 41.3 % in pretreated plants. Consistently, pretreated plants maintained higher photosynthetic rate during salt stress, suggesting the enhanced tolerance by salt priming. Salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 56 publications
(68 reference statements)
1
15
0
Order By: Relevance
“…SA can be used to promote plant growth under stress and non-stress conditions (Noreen et al 2009). As previously mentioned, salt priming can improve salt tolerance in sweet sorghum by enhancing osmotic resistance and reducing root Na + uptake (Yan et al 2015).…”
Section: Research On Agronomic Technologies For Enhancing Saline-alkamentioning
confidence: 82%
See 2 more Smart Citations
“…SA can be used to promote plant growth under stress and non-stress conditions (Noreen et al 2009). As previously mentioned, salt priming can improve salt tolerance in sweet sorghum by enhancing osmotic resistance and reducing root Na + uptake (Yan et al 2015).…”
Section: Research On Agronomic Technologies For Enhancing Saline-alkamentioning
confidence: 82%
“…The decreases in P n and T r under salt stress were found to be alleviated by silicon application (Liu et al 2015). Sorghum plants pretreated with salt maintained a higher P n during salt stress, suggesting that salt priming can enhance salt tolerance (Yan et al 2015).…”
Section: Photosynthesis and Fluorescence Propertiesmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, wheat (Triticum aestivum) exhibited improved drought tolerance after initial drought priming (Wang et al, 2014). Accumulating evidence has revealed that plants can also be primed for salt tolerance after seeds or seedlings are treated with salt (Yan et al, 2015;Pandolfi et al, 2016;Ali et al, 2017;Berhane and Chala, 2017). Although the mechanisms underlying saltinduced priming remain unclear, compared with naive (nonprimed) ones, primed plants show increased levels of organic solutes, such as proline (Pro) and sugars (Sivritepe et al, 2003), a higher photosynthetic rate (Yan et al, 2015), and increased abilities to sequester vacuolar sodium in the leaves and maintain low sodium content in the roots (Sivritepe et al, 2003;Nakaune et al, 2012;Yan et al, 2015;Pandolfi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most important metabolisms for plant growth, photosynthesis is sensitive to salt stress. Photosynthetic analysis seems to be an effective and convenient way for diagnosing plant salt tolerance, because photosynthetic capacity in susceptible cultivars is more liable to be inhibited than tolerant ones [17,18,19,20,21,22]. Salt-induced stomatal closure initially depressed photosynthesis by lowering CO 2 availability [23,24], and subsequently, the negative effect on Rubisco can further restrict CO 2 fixation [25,26].…”
Section: Introductionmentioning
confidence: 99%